2021
DOI: 10.17645/pag.v9i2.3923
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19: A Different Economic Crisis but the Same Paradigm of Democratic Deficit in the EU

Abstract: Based on a normative orientation and an interdisciplinary perspective, this is a comparative study, using the process tracing methodology, between the EU responses to Eurozone and Covid-19 crises to assess if, despite different outcomes, institutional decision-making processes evidence a change. The study concluded that the EU democratic deficit remains, which assumes special features in economic crises, providing a political oversize power to the economically hegemonic states, thus constraining ideological de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Others have found that the pandemic has not deepened existing democratic deficiencies. This case has been made the European Union [ 82 ] and some individual countries like the Czech Republic and Slovakia [ 73 , 79 ]. Lewkowicz et al [ 83 ], utilizing the V-Dem indices and the PanDem index, show that the stronger the rule of law and the higher levels of electoral democracy, the lower the risk of democratic backsliding has been in the face of the pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…Others have found that the pandemic has not deepened existing democratic deficiencies. This case has been made the European Union [ 82 ] and some individual countries like the Czech Republic and Slovakia [ 73 , 79 ]. Lewkowicz et al [ 83 ], utilizing the V-Dem indices and the PanDem index, show that the stronger the rule of law and the higher levels of electoral democracy, the lower the risk of democratic backsliding has been in the face of the pandemic.…”
Section: Resultsmentioning
confidence: 99%